Luxembourg : Financial Sector Assessment Program: Technical Note-Anti-Money Laundering And Combatting The Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations made in the 2017 Financial Sector Assessment Program (FSAP) Update for Luxembourg in the area of anti-money laundering and combating the financing of terrorism (AML/CFT). Since the last FSAP update, important steps have been taken to strengthen the AML/CFT regime. Luxembourg's risk profile appears to be evolving as a result of the authorities' push for increased tax transparency. Transparency of the beneficial ownership of legal persons has also improved. AML/CFT supervision has been strengthened in recent years, but challenges remain, including with respect to lawyers.